Going beyond energy intensity to understand the energy metabolism of nations: The case of Argentina - Recalde, Marina Yesica (2012)
The link between energy consumption and economic growth has been widely studied in the economic literature. Understanding this relationship is important from both an environmental and a socio-economic point of view, as energy consumption is crucial to economic activity and human environmental impact. This relevance is even higher for developing countries, since energy consumption per unit of output varies through the phases of development, increasing from an agricultural stage to an industrial one and then decreasing for certain service based economies.In the Argentinean case, the relevance of energy consumption to economic development seems to be particularly important. While energy intensity seems to exhibit a U-Shaped curve from 1990 to 2003 decreasing slightly after that year, total energy consumption increases along the period of analysis. Why does this happen? How can we relate this result with the sustainability debate? All these questions are very important due to Argentinean hydrocarbons dependence and due to the recent reduction in oil and natural gas reserves, which can lead to a lack of security of supply.In this paper we study Argentinean energy consumption pattern for the period 1990-2007, to discuss current and future energy and economic sustainability. To this purpose, we developed a conventional analysis, studying energy intensity, and a non conventional analysis, using the Multi-Scale Integrated Analysis of Societal and Ecosystem Metabolism (MuSIASEM) accounting methodology. Both methodologies show that the development process followed by Argentina has not been good enough to assure sustainability in the long term. Instead of improving energy use, energy intensity has increased. The current composition of its energy mix, and the recent economic crisis in Argentina, as well as its development path, are some of the possible explanations.